Pengaruh Kegiatan Pembiasaan Religi Dan Pembinaan Karakter Terhadap Prilaku Religius Siswa Di SMP Adhyaksa Medan - Ginting, Shynta Sri Wahyuni; Nahar, Syamsu; Hanum OK, Azizah (Kamaya: Jurnal Ilmu Agama, 2024)
Implementing habituation activities is something that is very important for every individual in forming character. Considering that in this era the decline in student ethics and morals is caused by various factors, apart from that in public schools, the portion available for studying Islam is limited to only 3 hours of lessons (JP) every week, of course these 3 hours of lessons are a short time for guiding students to have noble character by always carrying out God's commands. This is different from Madrasah schools which under the auspices of the Ministry of Religion receive a large portion of Islamic religious learning, because in Madrasahs Islamic religious learning is divided based on their respective fields. With these clear differences, Adhyaksa Medan Middle School carries out a program of religious habituation and character development activities. The aim of this research is to reveal the influence of religious orientation and character development activities on students' religious behavior. This research used quantitative methods, the sample was 42 students. The data in this research was obtained through questionnaire results. From the results of the research, several important findings were found, firstly, there was a significant influence between religious habituation activities on the religious behavior of students at Adhyaksa Medan Middle School, as shown by the results of the t test that the significance value of Religious Habituation Activities on Students' Religious Behavior was 0.000 < 0.05 and the t_count value was 8.548 > ttable 2.022, secondly, it can be seen that there is a significant influence of character development activities on the religious behavior of Medan Adhyaksa Middle School students, as shown by the results of the t test that the significance value of Character Development Activities on Religious Behavior is 0.000 < 0.05 and the t_count value is 5.772 > ttable 2.022, and thirdly there is an infl/ /uence of Activities religious habituation and character development simultaneously (simultaneously) on religious behavior in Adhyaksa Medan Middle School students is shown by the results of the F test that the significance value for the influence of X1 and 3.24.